Interaksi Tanaman Kacang Tanah (Arachis hypogeae) dalam Agroforestri Interaction Of Peanuts (Arachis hypogeae) In Agroforestri - Fahruni Fahruni (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2018)
Nutrient availability in the forest soils is affected by forest degradation and deforestation as forest conversion. Peanut (Arachis hypogaea) is included LeguminalesOrdo and able to supply nutrient from the plant parts. As intercrops in agroforestry patterns, peanuts provide interaction for the surrounding soil and plants. The purpose of this research is to know the interaction of peanut plants on nutrient availability and on the growth of rubber plant (Heveabrasiliensis Muell, Arg.) on agroforestry pattern. This research was conducted at the Banjarbaru through the observation of rubber plant growth and soil analysis. Research result shows that peanuts can increase the availability of nutrients in the soil. The N element increases from 0.16% to 0.45%, thereby stimulating vegetative growth (green) such as leaves. The P element increases from 5.57 mg/100gr to 8.93 mg/100gr, the K element increases from 15.87 mg/100gr to 41.50 mg/100 gr, and organic C increased from 0.83% to 1.55%. The interaction of peanut crops as intercropping plants was able to give high impact to the height of the rubber plant, namely 77.68 cm. The impact on the growth of rubber plant diameter also increased by 0.59 cm compared to only the rubber pattern of 0.28 cm.